Molecular modeling and small angle X-ray scattering studies of Hoplosternum littorale cathodic haemoglobin - Peres, P.; Lombardi, F. R.; dos Santos, G. C.; Olivieri, JR; Canduri, F.; Bonilla-Rodriguez, G. O.; de Azevedo, W. F. (Elsevier B.V., 2004)
Considerable interest is currently focused on fish haemoglobins in order to identify the structural basis for their diversity of functional behavior. Hoplosternum littorale is a catfish that presents bimodal gill (water)/gut (air) -breathing, which allows this species to survive in waters with low oxygen content. The hemolysate of this fish showed the presence of two main haemoglobins, cathodic and anodic. This work describes structural features analyzed here by integration of molecular modeling with small angle X-ray scattering. Here is described a molecular model for the cathodic haemoglobin in the unliganded and liganded states. The models were determined by molecular modeling based on the high-resolution crystal structure of fish haemoglobins. The structural models for both forms of H. littorale haemoglobin were compared to human haemoglobin. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: catfish; cathodic haemoglobin; Hoplosternum littorale; molecular modeling; SAXS; bioinformatics; Structure